ISNAR Annual Report 1999 - International Service for National Agricultural Research (International Service for National Agricultural Research, 2000)
ISNAR's 1999 Annual Report explores the theme of agricultural research capacity building through the lens of ISNAR's work to strengthen NARS in developing countries. It focuses on two distinct levels of capacity building: first the level of the individual researcher or research manager and second the organizational level.